Virus Matryoshka: A Bacteriophage Particle—Guided Molecular Assembly Approach to a Monodisperse Model of the Immature Human Immunodeficiency Virus. Issue 42 (16th September 2016) - Saxena, Pooja; He, Li; Malyutin, Andrey; Datta, Siddhartha A. K.; Rein, Alan; Bond, Kevin M.; Jarrold, Martin F.; Spilotros, Alessandro; Svergun, Dmitri; Douglas, Trevor; Dragnea, Bogdan
Abstract : Immature human immunodeficiency virus type 1 (HIV‐1) is approximately spherical, but is constructed from a hexagonal lattice of the Gag protein. As a hexagonal lattice is necessarily flat, the local symmetry cannot be maintained throughout the structure. This geometrical frustration presumably results in bending stress. In natural particles, the stress is relieved by incorporation of packing defects, but the magnitude of this stress and its significance for the particles is not known. In order to control this stress, we have now assembled the Gag protein on a quasi‐spherical template derived from bacteriophage P22. This template is monodisperse in size and electron‐transparent, enabling the use of cryo‐electron microscopy in structural studies. These templated assemblies are far less polydisperse than any previously described virus‐like particles (and, while constructed according to the same lattice as natural particles, contain almost no packing defects). This system gives us the ability to study the relationship between packing defects, curvature and elastic energy, and thermodynamic stability. As Gag is bound to the P22 template by single‐stranded DNA, treatment of the particles with DNase enabled us to determine the intrinsic radius of curvature of a Gag lattice, unconstrained by DNA or a template. We found that this intrinsic radius is far larger than that of a virion or P22‐templated particle. We conclude that Gag is under elastic strain in a particle; this has important implications for the kinetics of shell growth, the stability of the shell, and the type of defects it will assume as it grows. Abstract : Collective properties such as bending stress may be an integral part of virus function, yet such properties are challenging to infer from conventional structural biology investigations. A novel approach is presented for crystallizing the structural proteins of a pleiomorphic virus on the quasispherical surface of a monodisperse virus. The approach leads to the first estimate of the intrinsic radius of curvature of the HIV Gag lattice.